Penerimaan dan Resiliansi Ibu dengan Anak Tuna Rungu - kurniawati, dewi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2024)
Every mother hopes to give birth to a perfect, normal, and healthy child, hope arises from the moment the child is still in the womb. Things turned around when the mother heard the diagnosis of her child with special needs. The purpose of this study was to see the picture, process, and factors of self-acceptance of mothers with children with special needs. This type of research uses qualitative with Life History. Data collection techniques use observation of family activities and interactions, in-depth interviews and document studies. Data collection was conducted from November 2022 to January 2023. The data obtained are analyzed using thematic analysis techniques inductively.